Attitudes to justice in a rural community. (2nd January 2018) - Newman, Daniel
Abstract : This paper offers a timely investigation into access to justice in rural areas through place-based research. The paper reports an empirical study designed to gain the local knowledge and personal experience of one particular group of rural dwellers in the hope that it might help encourage a wider discussion on access to rural justice. The research has been conducted within the wider socio-political context of austerity that provides a challenge to public-sector service delivery in general, alongside the particular legal impact of budget cuts on the provision of justice, with closures of large amounts of courts, the decline in legal aid provision and reductions in police numbers. Such are important issues for England and Wales as a whole, meaning that this research is contemporary and represents one of the first academic studies to specifically deal with the impact of austerity on access to justice. The value of this research is further heightened with its focus on the specific rural impact of such cuts as rural areas are those likely to face the biggest effect on provision while concomitantly being the least studied area of legal provision, with notably little scholarship in the past two decades into justice in rural England and Wales. Considering the damage these cuts may cause to rural justice is a current issue of utmost importance to the principle of access to justice. The paper offers the foundations upon which a new wave of academic attention to justice in rural areas should be developed, reflecting the need to give due credence to the rural in contemporary socio-legal scholarship.